2006
DOI: 10.1186/1741-7007-4-11
|View full text |Cite
|
Sign up to set email alerts
|

Polyphyly and gene flow between non-sibling Heliconius species

Abstract: Background: The view that gene flow between related animal species is rare and evolutionarily unimportant largely antedates sensitive molecular techniques. Here we use DNA sequencing to investigate a pair of morphologically and ecologically divergent, non-sibling butterfly species, Heliconius cydno and H. melpomene (Lepidoptera: Nymphalidae), whose distributions overlap in Central and Northwestern South America.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(57 citation statements)
references
References 77 publications
(108 reference statements)
6
50
1
Order By: Relevance
“…Finally, our approach could also be extended to scan the genome for regions that contribute to reproductive isolation Bull et al 2006;Geraldes et al 2006;Miller et al 2006). Indeed, models of parapatric speciation predict that loci involved in the formation of species will experience no or little gene flow since the split and therefore have more fixed differences and fewer shared alleles than do background loci.…”
Section: Discussion Advantages and Limitations Of Mimarmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, our approach could also be extended to scan the genome for regions that contribute to reproductive isolation Bull et al 2006;Geraldes et al 2006;Miller et al 2006). Indeed, models of parapatric speciation predict that loci involved in the formation of species will experience no or little gene flow since the split and therefore have more fixed differences and fewer shared alleles than do background loci.…”
Section: Discussion Advantages and Limitations Of Mimarmentioning
confidence: 99%
“…The parameters are estimated from all the polymorphism data at a single locus (Nielsen and Wakeley 2001) or at multiple loci , using Markov Chain Monte Carlo (MCMC). The Hey and Nielsen method, henceforth called IM, has been applied to a number of species, from Heliconius (Bull et al 2006) to cichlids . These applications suggest that speciation often occurs in the presence of some gene flow (Hey 2006).…”
mentioning
confidence: 99%
“…Hybridization in Heliconius has hitherto been examined genetically only in a few cases that involve closely related species: Heliconius erato and Heliconius himera, or Heliconius melpomene and Heliconius cydno (Jiggins et al 1997;Bull et al 2006;Kronforst et al 2006). In all other cases, inferences of hybridization have been made on the basis of phenotypes of wildcaught specimens.…”
Section: Introductionmentioning
confidence: 99%
“…To support the hypothesis of interspecific gene exchange, several studies [22,[83][84][85] have invoked as evidence of hybridization and introgression similar alleles shared among Heliconius species in gene genealogies of various nuclear protein-coding loci (mannose phosphate isomerase, triose phosphate isomerase, distalless, invected, white and scalloped). A limitation of these studies is that each compared variability among species only at one or a few geographical localities.…”
Section: Primer On Selection For Müllerian Mimicry Among Heliconius Smentioning
confidence: 99%
“…Brower [20] combined data for each of these genes in global analyses encompassing multiple geographical regions, and found that many of the 'introgressed' alleles are distributed widely among members of the H. cydno-H. melpomene clade from throughout their geographical ranges, a pattern explained at least as well by retention of ancestral polymorphism as by recent introgressive hybridization [86,87]. Thus, oft-cited claims of ongoing, evolutionarily significant gene flow between H. cydno and H. melpomene [83,84,88] should be viewed with circumspection (as suggested by Kronforst et al [89]). …”
Section: Primer On Selection For Müllerian Mimicry Among Heliconius Smentioning
confidence: 99%